2015
DOI: 10.1038/srep17265
|View full text |Cite
|
Sign up to set email alerts
|

Laser jetting of femto-liter metal droplets for high resolution 3D printed structures

Abstract: Laser induced forward transfer (LIFT) is employed in a special, high accuracy jetting regime, by adequately matching the sub-nanosecond pulse duration to the metal donor layer thickness. Under such conditions, an effective solid nozzle is formed, providing stability and directionality to the femto-liter droplets which are printed from a large gap in excess of 400 μm. We illustrate the wide applicability of this method by printing several 3D metal objects. First, very high aspect ratio (A/R > 20), micron scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 44 publications
0
84
0
Order By: Relevance
“…Laser-induced transfer, which relies on the energy of an incident laser pulse to transfer a deposit (or variously termed voxel) of material (the donor) from a carrier substrate towards a receiver substrate, encompasses a range of techniques for rapid microfabrication of electronic, photonic and biomedical devices [1][2][3][4][5]. Recent results have shown the lateral shaping of deposits in a dynamic fashion for laser-induced forward transfer (LIFT), via the use of a digital micromirror device (DMD) acting as a spatial light modulator [6,7], hence enabling the rapid prototyping of complex shapes with micron-scale fabrication resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced transfer, which relies on the energy of an incident laser pulse to transfer a deposit (or variously termed voxel) of material (the donor) from a carrier substrate towards a receiver substrate, encompasses a range of techniques for rapid microfabrication of electronic, photonic and biomedical devices [1][2][3][4][5]. Recent results have shown the lateral shaping of deposits in a dynamic fashion for laser-induced forward transfer (LIFT), via the use of a digital micromirror device (DMD) acting as a spatial light modulator [6,7], hence enabling the rapid prototyping of complex shapes with micron-scale fabrication resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the copper structure serves as a template to precisely define the shape and size of the channel inside the hydrogel tubular networks. Third, the available techniques [39][40][41][42][43][44] to mass-produce 3-D microstructures in copper make our method scalable (however, in this work, we simply used hand-made copper templates for demonstration). Finally, we successfully developed a convenient and cost-efficient method to replace the copper ions with calcium ions to eliminate the potential toxicity that the copper ions may have on cells.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38] To create branched 3-D tubular structures made of hydrogel, we employed a copper template that could be prepared by reported mass-production strategies [39][40][41] or recent 3-D printing strategies. [42][43][44] We immersed the copper template in alginate, a natural polysaccharide derived from brown sea algae, which has been widely used to fabricate bio-scaffolds in biomedical and biological applications; 19,45-49 then we conducted electrolysis, during which the released copper ions from the template quickly cross-linked the alginate in the solution and formed gel. The reaction was so quick that all the generated Cu 2þ ions were consumed before diffusing away, resulting in a uniform thin layer of hydrogel coating covering the copper template.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond a certain radiant exposure, the irradiation leads to rapid heating, followed by changes in metal film phase due to explosive boiling, and formation of a bubble of the vaporized material . Previous reports on imaging of the ejection process during laser irradiation of gold films suggested that propulsion of the material can be characterized as a fast jetting or protrusion of molten Au with ejection velocities of approximately tens to several hundreds of m/s depending on the radiant exposure used . This implies that a fast directional velocity can be achieved by the jetting molten Au, enabling the injection of the particles through the biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain a uniform damage throughout the entire biofilm, our approach is to utilize the effects of laser pulse interaction with gold films to induce both photothermal and mechanical damage to the surrounding biofilm structure. Pulsed laser interaction on metal thin films has been previously utilized as a means to transfer metallic patterns with controlled dimensions and precise nanostructures . The absorption of the laser energy by the metal film leads to non‐uniform heating and localized melting of the film resulting to its ejection to an adjacent substrate .…”
Section: Introductionmentioning
confidence: 99%